Aortic Elasticity and Cardiac Function in Fetuses With Aortic Coarctation - Zhou, Dan; Xu, Ran; Zhou, Jiawei; Xie, Li; Xu, Ganqiong; Liu, Minghui; Zeng, Shi (Frontiers in Cardiovascular Medicine, 2022)
Objective: The purpose of the study was to observe the elasticity of the ascending aorta (AAo) in normal fetuses and fetuses with coarctation of the aorta (CoA) by M-mode echocardiography. Methods: This was a prospective clinical study performed in 16 fetuses with CoA and 48 gestational-age matched normal fetuses. The minimum internal diameter in the diastolic phase (Dmin) and the maximum internal diameter in the systolic phase (Dmax) of the AAo were measured by M-mode echocardiography. Aortic strain was calculated using the formula "100×(Dmax-Dmin)/Dmin)" . Doppler echocardiography was performed to measure the cardiac function parameters. Correlations between aortic strain and cardiac function were assessed in fetuses with CoA. Results: The aortic strain of the ascending aorta in the fetuses with CoA was significantly lower than that in normal fetuses (18.12±4.88% vs. 25.22±4.92%, p<0.01). The fetuses with CoA showed significantly higher combined cardiac output than the controls (471.89±93.98 vs. 411.57±46.35 ml/min/kg, p<0.05). Compared with the normal group, the early diastole velocities (E’) and peak systolic velocities (S’) of the left side were obviously decreased in the CoA group (p<0.05), while the left E/E’ was significantly increased in the fetuses with CoA (p<0.01). For the fetuses with CoA, the aortic strain of the AAo was correlated with the left E/E’ and S’ (r= -0.522 and 0.504, respectively, P<0.05). Conclusions: The aortic strain of the ascending aorta was significantly decreased in fetuses with CoA in middle-late gestation. The impaired strain of the ascending aorta was correlated with left ventricle function in the fetuses with CoA. These findings might imply that the intrinsic aortic wall abnormalities of CoA might develop early in utero.